Analisis Tingkat Kerawanan Kebakaran Hutan dan Lahan di Kabupaten Bengkalis Tahun 2019 Dan 2023: Analysis of Forest and Land Fire Vulnerability Levels in Bengkalis Regency in 2019 and 2023 - Bakara, Teguh; Saharjo, Bambang Hero; Nurhayati, Ati Dwi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Forest and land fires occur every year in Bengkalis Regency, indicated by hotspots and burned areas. One of the strategies to reduce these incidents is to map areas prone to fires. The method to mapping the vulnerability level of forest and land fires is scoring based on BNPB Regulation No. 2 of 2012 with three indicators: rainfall, soil type, and land cover. The results showed that the number of hotspots in 2019 and 2023 in Bengkalis Regency was 1703 points and 2019 had the most hotspots, which was 1060 points. The burned area in 2019 was recorded at 13,496.49 hectares, wider than in 2023. The majority of the Bengkalis Regency area is included in the high vulnerability category, namely 53.09% in 2019 and 54.98% in 2023.